2011
DOI: 10.1016/j.jvoice.2009.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Practice Variability on Learning of Relaxed Phonation in Vocally Hyperfunctional Speakers

Abstract: The present study investigated the effects of practice variability on the learning of relaxed phonation using a motor learning perspective. Twenty-one individuals with hyperfunctional voice problems were evenly and randomly assigned to three groups of practice conditions: constant, blocked, and random practice conditions. During training, participants in the constant practice condition were asked to read aloud sentence stimuli with four Chinese characters. Participants in the blocked practice condition were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 14 publications
1
31
0
8
Order By: Relevance
“…Although some studies reported findings consistent with the motor learning literature [14••,41,47], others failed to find clear and consistent differences between conditions [42,43,45,51,52], or reported opposite effects for some participants [22•,44]. It is likely that differences in tasks, measures, and populations contribute to this mixed pattern.…”
Section: Speech Motor Control and Learningmentioning
confidence: 97%
See 1 more Smart Citation
“…Although some studies reported findings consistent with the motor learning literature [14••,41,47], others failed to find clear and consistent differences between conditions [42,43,45,51,52], or reported opposite effects for some participants [22•,44]. It is likely that differences in tasks, measures, and populations contribute to this mixed pattern.…”
Section: Speech Motor Control and Learningmentioning
confidence: 97%
“…For individuals with speech/voice impairments, studies have examined practice amount [14••], practice schedule [22•,41,42], practice variability [43], practice distribution (massed vs. distributed) [42,44,45], feedback type (verbal knowledge of results vs. biofeedback knowledge of performance) [46], feedback frequency [21,47–51], feedback timing (immediate vs. delayed) [48] and attentional focus [52]. Although some studies reported findings consistent with the motor learning literature [14••,41,47], others failed to find clear and consistent differences between conditions [42,43,45,51,52], or reported opposite effects for some participants [22•,44].…”
Section: Speech Motor Control and Learningmentioning
confidence: 99%
“…In speech-related research, Ballard, Maas, and Robin (2007) observed positive treatment effects when including variable practice for adults with acquired apraxia of speech. Studies that have directly compared constant vs. variable practice in speech treatment have found mixed results; Wong, Ma and Yiu (2011) reported no advantage for practice variability among individuals with hyperfunctional voice problems but Adams and Page (2000) observed an advantage for variable practice in motor speech learning in healthy adults. However, there is no systematic exploration of this principle of practice variability among speech motor learning in individuals with RSSEs.…”
Section: Motor Learningmentioning
confidence: 99%
“…However, role of PMLs in speech-motor learning [8][9][10][11][12][13][14] . An aspect of PMLs to have gained considerable attention in speechmotor learning is practice variability [8,15,16] . Practice variability can range from practicing just one variant of a motor skill (constant practice) to practicing 2 or more variants of the same motor skill (variable practice).…”
Section: Introductionmentioning
confidence: 99%